Blood pressure and risk of dementia and its subtypes: a historical cohort study with long‐term follow‐up in 2.6 million people. (18th July 2019) - Gregson, J.; Qizilbash, N.; Iwagami, M.; Douglas, I.; Johnson, M.; Pearce, N.; Pocock, S.
Abstract : Background and purpose: Elevated blood pressure (BP) is prevalent and modifiable and has been hypothesized to lead to increased risk of dementia. Data: Data on 2 593 629 people from the UK Clinical Practice Research Database aged ≥40 years with a BP measurement between 1992 and 2011 and no prior record of dementia were collected. Methods: Poisson regression models were used to study the association between BP and physician‐diagnosed dementia. BP is believed to fall during the prodromal phase of dementia development, so associations were investigated by categories of time since BP measurement (<5, 5–10, >10 years) and by subtypes of dementia. Results: During a median follow‐up of 8.2 years, 65 618 cases of dementia were observed: 49 161 Alzheimer's, 13 816 vascular dementia and 2541 other subtypes. For each 10 mmHg higher systolic BP, the future dementia risk was 9.2% (95% confidence interval 8.4%–10.0%) lower, but this association varied markedly by time since BP measurement. Short‐term associations with dementia were inverse with a 15.8% (15.5%–17.0%) lower risk 0–5 years after BP measurement and a 5.8% (7.7%–4.4%) lower risk 5–10 years after BP measurement. During the period >10 years after BP measurement, dementia risk was only 1.6% (0.1%–3.0%) lower, with a 4.3% (2.5%–6.0%) lower risk of Alzheimer's disease and a 7.0% (3.8%–10.2%) higher risk of vascular dementia. Conclusions: Elevated BP is associated with decreased risk of dementia in the short term, possibly due to reverse causation. Long‐term associations of BP with dementia are less marked and differ by dementia subtype.